2011
DOI: 10.1177/0961203311422724
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD247 with systemic lupus erythematosus in Asian populations

Abstract: A significant association between variants in CD247 and SLE was demonstrated in Asian populations. Understanding the involvement of CD247 in SLE may shed new light on disease mechanisms and development of new treatment paradigms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
2
16
0
2
Order By: Relevance
“…Our most significant findings are consistent with those from a previous report in Asian populations (11) that resulted from the examination of GWAS data (19). In these studies, 14 SNPs in the CD247 gene locus (including both upstream and downstream regions of the gene) were found to be significantly associated with SLE, five of which were inside the CD247 gene (personal communication from authors of (19), May 2012), all located in intron 1 (as indicated by the dark blue dots in Figure 1).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our most significant findings are consistent with those from a previous report in Asian populations (11) that resulted from the examination of GWAS data (19). In these studies, 14 SNPs in the CD247 gene locus (including both upstream and downstream regions of the gene) were found to be significantly associated with SLE, five of which were inside the CD247 gene (personal communication from authors of (19), May 2012), all located in intron 1 (as indicated by the dark blue dots in Figure 1).…”
Section: Resultssupporting
confidence: 93%
“…In contrast, our discoveries highlight genetic association in Asians in the 5’ region (intron1) of CD247 . This is consistent with recent studies performed in Asian populations (11). Considering the ethnic heterogeneities in the epidemiology of SLE (12,13), these observations suggest a particular association of CD247 genetic variants in Asian populations.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…been extremely successful in identifying susceptibility loci for many disease phenotypes, including SLE [8][9][10][11][12][13][14][15] and related endophenotypes. 16,17 Herein, we report the first large-scale GWAS to identify loci predisposing to LN among women with SLE.…”
mentioning
confidence: 99%